The Success of Women Entrepreneur: Influence of Entrepreneurship Education, Access to Capital, Technology Adoption, Family Support, and Business Network - Sangaji, Joko (IJBLE Scientific Publications Community Inc., 2025)
This study aims to identify and analyze the influence of entrepreneurship education, access to capital, technology adoption, family support, and business networks on the success of MSMEs managed by women in urban areas of Indonesia. A quantitative approach was used with a descriptive and causal design. The sample consisted of 150–200 female entrepreneurs in the Jabodetabek, Bandung, and Surabaya areas, obtained through purposive sampling techniques. Data were collected using questionnaires and analyzed using multiple linear regression. The results of the study are expected to provide theoretical and practical implications in supporting women's empowerment in the MSME sector.